Comparison of the Effectiveness of Botulinum Toxin A (BoNTA) Injection Therapy and Deep Brain Stimulation (DBS) in Cervical Dystonia: A Meta-Analysis - Purbawijaya, Poek Denny; Tumewah, Rizal; Jehosua, Seilly Yunita; Warouw, Finny; Runtuwene, Theresia (Eduvest - Journal of Universal Studies, 2025)
Cervical dystonia is a debilitating movement disorder, and both Deep Brain Stimulation (DBS) and Botulinum Toxin A (BoNTA) are commonly used treatments. However, their comparative effectiveness remains unclear. This study aims to evaluate the effectiveness of DBS versus BoNTA in improving TWSTRS scores and to explore factors influencing treatment outcomes. A meta-analysis was conducted, including subgroup analyses and meta-regression to assess the efficacy of both treatments across various demographics and study designs. The results indicate that DBS significantly improves TWSTRS scores by an average of 54.48% (95% CI 45.01–63.95), compared to BoNTA’s 28.96% (95% CI 24.12–33.80). High heterogeneity was noted, but no significant differences were found across intervention types or patient demographics. These findings suggest that DBS is a more effective treatment for cervical dystonia than BoNTA, regardless of patient age or follow-up duration. Future research should investigate the mechanisms behind these differences to optimize treatment strategies.